2016
DOI: 10.1080/2159256x.2016.1240748
|View full text |Cite
|
Sign up to set email alerts
|

Transposable elements and circular DNAs

Abstract: Circular DNAs are extra-chromosomal fragments that become circularized by genomic recombination events. We have recently shown that yeast LTR elements generate circular DNAs through recombination events between their flanking long terminal repeats (LTRs). Similarly, circular DNAs can be generated by recombination between LTRs residing at different genomic loci, in which case the circular DNA will contain the intervening sequence. In yeast, this can result in gene copy number variations when circles contain gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…In many model organisms, such as Drosophila , yeast, and human cell lines, large segmental deletions were previously found to be facilitated by ectopic recombination between tandemly arrayed repeat sequences (59, 60). This mechanism is particularly interesting in the context of HGT, as these recombination events often result in the formation of circular extrachromosomal DNA (61, 62).…”
Section: Discussionmentioning
confidence: 99%
“…In many model organisms, such as Drosophila , yeast, and human cell lines, large segmental deletions were previously found to be facilitated by ectopic recombination between tandemly arrayed repeat sequences (59, 60). This mechanism is particularly interesting in the context of HGT, as these recombination events often result in the formation of circular extrachromosomal DNA (61, 62).…”
Section: Discussionmentioning
confidence: 99%
“…The consistency between eccDNAs generated through recombination events within the genome and their recombination junctions supports the possibility that retrotransposable elements may move around the genome through DNA circularization [ 52 ]. EccDNAs from DNA circularization result in gene copy number variations when circles contain genes and origins of replication [ 53 ], which contributes to additional gain of novel functions. For example, a previous study revealed the eccDNA-based amplification and transmission of herbicide resistance in the crop weed Amaranthus palmeri [ 54 ].…”
Section: Biogenesis and Replication Of Eccdnamentioning
confidence: 99%
“…EccDNAs are produced in both physiological and pathological conditions. For eccDNAs in normal cells, like the eccDNAs containing transposable elements and the extrachromosomal ribosomal DNA circles in yeast (4, 41, 42), their presence may be related to genome plasticity during development and aging (25). In pathological conditions, eccDNAs are found to play roles in human diseases and disease treatments, especially for larger eccDNAs (episomes and DMs) with their functions being better characterized.…”
Section: Implications Of Eccdnas In Human Diseases and Treatmentsmentioning
confidence: 99%